A Bridge or a Wall: Teachers Mediating ICT in the Classroom - Gertha Teidla-Kunitsõn; Merike Sisask; Halliki Põlda (MDPI AG, 2023)
While information and communication technology (ICT) has changed every aspect of our lives and will continue to do so, it is the role of education to prepare students adequately for their future adult lives in the digital age. This places high expectations on teachers. This article aims to provide an understanding of how teachers' attitudes towards ICT in the classroom are reflected in the regular use of ICT in their daily teaching practices and how teachers describe their role in preparing young people for adult life in the digital age. Data from the DigiGen project are used, which entails in-depth semi-structured interviews with eight general-education (grades 1-12) teachers from Estonia. The results indicate that teachers' attitudes vary-while some perceive ICT as a natural part of life, others have more moderate or even sceptical attitudes towards ICT use in the classroom. Teachers' practices in using ICT in the classroom differ greatly, but most are monotonous, putting students in a passive role. Teachers understand their role in preparing young people for adult life in the digital age as important, although this is not reflected in their practices.